Student Perceptions of Classroom Environments in Streamed Middle Secondary Mathematics Classes in Australian Christian Schools - Kilgour, Peter; Rickards, Anthony (Key Centre for School Science and Mathematics, Curtin University of Technology, 2008)
This paper reports on a study into the perceptions students have of the learning environment in Year 9 and 10 mathematics classrooms when the classes are streamed. The sample consisted of 581 students in Years 9 and 10 in 7 different Christian independent schools across Australia. The What is Happening in the Classroom (WIHIC) inventory was used along with a qualitative analysis of interviews with a subset of participants. Results included: students in lower stream mathematics classes report significantly less positive perceptions of their classroom learning environments than students in upper stream mathematics classes, the areas rated most negatively by the lower stream students were in teacher support and task orientation, the areas rated most negatively by the upper stream students were in involvement and investigation, students in the upper stream often feel overworked and left behind whereas students in the lower stream are in some cases not encouraged to excel and fall into a fatalistic attitude of underachievement, even though the learning environment in upper streams was perceived by students to be more positive than lower streams, the desire for positive changes in the upper stream learning environment was more pronounced than in the lower stream. Another result of particular interest and concern was that lower stream perceptions of learning environment deteriorates from Year 9 to Year 10 whereas upper stream perceptions become more positive from Year 9 to Year 10.